Avian Virtual Gallery (Aviavista) as a Tool for Promoting Avitourism at Bandar Universiti Pagoh - Bahman, Nur Alia Arisa; Norazlimi, Nor Atiqah; Lokman, Mohd Ilham Norhakim (Enhanced Knowledge in Sciences and Technology, 2025)
Bandar Universiti Pagoh (BUP) has abundant bird biodiversity making it a great destination for edutourism and avitourism. This study intended to promote avitourism and edutourism at Bandar Universiti Pagoh by developing Aviavista, an avian virtual gallery. The platform uses immersive and interactive virtual experiences to highlight the region’s unique avian biodiversity, focusing on bird enthusiasts, researchers, students, and tourists. Aviavista addresses the absence of creative tools for engaging visitors by highlighting the distinctive qualities of local bird species while promoting environmental awareness and sustainable tourism practices. Traditional ways of promoting avitourism and edutourism may not be able to fully use technological advancements in order to fulfil the changing demands of potential visitors. This virtual gallery allows users to discover many bird species located at Bandar Universiti Pagoh from anywhere. The project entailed gathering a comprehensive list of bird varieties in BUP, creating a user-friendly digital interface, and assessing the platform’s effectiveness based on user feedback. 33 bird species were recorded throughout this study in BUP using visual and auditory methods. Aviavista, an avian virtual gallery was developed using Artstep platform. The survey was conducted to evaluate the effectiveness of Aviavista in promoting avitourism and edutourism in BUP. The findings show that Aviavista successfully boosts biodiversity awareness, improves educational outcomes, and generates interest in avitourism, despite ongoing constraints such as digital literacy, user involvement, and funding. Future developments include optimising the platform’s design, increasing community interaction, and organising conservation-focused events. This study emphasises the potential of technology-enhanced instruments to promote ecotourism and biodiversity conservation.